Immunohistochemical and Electron Microscopic Study of the Inhibitory Effects of Olive Oil Polyphenol on Dexamethasone-Induced Apoptosis - Ali Reza Khalatbary; Behrooz Mohammadnegad; Ghazaleh Goudarzi; Ali Fazlollahpour Balef (Iranian Society of Pathology, 2017)
Background: There is accumulating evidence that a polyphenol present in olive oil, oleuropein, has antioxidant, anti-inflammatory and anti-apoptotic effects. This study aimed at determining the anti-apoptotic effect of Oleuropein (Ole) on dexamethasone-induced apoptosis of mouse thymocytes. Method: Mice were randomly divided to four groups as follow: Dexamethasone (Dex)-treated group (20 mg/kg; single dose), Ole-treated group (20 mg/kg per day), Dex plus Ole-treated group, and vehicle group. Sections of thymus were taken 16 hours after dexamethasone injection and studied for histopathological and immunohistochemistry assessment. Result: Further characteristics of degeneration in thymocytes were observed in the Dex group compared with the Dex plus Ole group. Compared with the Dex group (10.94±3.35), positive staining for Bax in thymocytes decreased in Dex plus Ole group (2.64±1.26), but remained higher than the Ole (0.65±0.30) and vehicle (0.67±0.29) groups. Compared with the Dex group (2.94±0.42), positive staining for Bcl-2 in thymocytes increased in Dex plus Ole group (12.24±1.84) yet was lower than the Ole (14.94±1.54) and vehicle (18.93±3.54) groups. Conclusion: Our results suggest that dexamethasone-induced apoptosis is subsided by oleuropein.